2021
DOI: 10.3390/ijms222413598
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Smad7-Mediated Transcription in Mouse Embryonic Stem Cells

Abstract: Smad7 has been identified as a negative regulator of the transforming growth factor TGF-β pathway by direct interaction with the TGF-β type I receptor (TβR-I). Although Smad7 has also been shown to play TGF-β unrelated functions in the cytoplasm and in the nucleus, a comprehensive analysis of its nuclear function has not yet been performed. Here, we show that in ESCs Smad7 is mainly nuclear and acts as a general transcription factor regulating several genes unrelated to the TGF-β pathway. Loss of Smad7 results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In agreement with this hypothesis lncSmad7 knockout resulted in the reduction of acetylation in several genomic loci ( Supplementary Figure S4A ). To verify the hypothesis that lncSmad7 regulates the transcription of other genes besides Smad7 , we first sought to uncouple the contribution to gene expression of lncSmad7 from those regulated by Smad7 ( 60 ). To this end, we compared the RNA expression profiles of WT ESCs with lncSmad7 KO, and the lncSmad7 KO ectopically expressing either lncSmad7 or Smad7 ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this hypothesis lncSmad7 knockout resulted in the reduction of acetylation in several genomic loci ( Supplementary Figure S4A ). To verify the hypothesis that lncSmad7 regulates the transcription of other genes besides Smad7 , we first sought to uncouple the contribution to gene expression of lncSmad7 from those regulated by Smad7 ( 60 ). To this end, we compared the RNA expression profiles of WT ESCs with lncSmad7 KO, and the lncSmad7 KO ectopically expressing either lncSmad7 or Smad7 ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that Smad7 can act as a general transcription factor regulating several genes that are unrelated to the TGF-β1 pathway [ 23 ]. Therefore, we next evaluated whether the reduced Stat3 content seen in Smad7-deficient cells was secondary to the regulation of Stat3 RNA expression by Smad7.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of Smad7 to act as a transcription factor has been previously shown in prostatic cancer cells, where Smad7 can bind the regulatory regions and enhance the expression of c-Jun and Histone deacetylase 6, two tumor-promoting genes [ 18 ]. Along the same lines is the demonstration that in mouse embryonic stem cells, Smad7 occupies the promoters of highly expressed key stemness regulators genes by binding to a specific consensus response element, NCGGAAMM [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, macrophage-specific SMAD7 deletion did not affect alanine aminotransferase (ALT) and aspartate transferase (AST) levels, inflammatory cell infiltration, and fibrosis degree in CCL 4 -induced chronic liver injury mouse models 101 . In addition, the evidence also demonstrates that SMAD7 can bind to the self-renewal genes Nanog, sex determining region Y-box 2 (Sox2), and inhibitor of DNA binding 2 (ID2) in embryonic stem cells (ESCs), regulating the self-renewal and pluripotency of ESCs 102 .…”
Section: The Functional Role Of the Tgf-β/smad Signaling Pathway In Hccmentioning
confidence: 99%